Understanding sexual prejudice among midwestern pre-service and in-service teachers - Foy, Joelyn Katherine (Kansas State University, 2014)
Sexual orientation is only one facet of diversity (Banks et al., 2005), but teacher preparation may not adequately address sexual prejudice (Lamb, 2013). Sexual prejudice arises when heterosexuality is assumed to be the default for all students. School environments reinforce heteronormativity (Dean, 2010; Foucault, 1990; Himmelstein & Bruckner, 2011) such that when hate speech or physical violence occur against the non-hetersexual or the transgender student, teachers may not be prepared to respond appropriately. Prejudice toward gender or sexually variant students may not be adequately addressed in teacher preparation to challenge the reproduction of heteronormativity in school environments. A mixed method approach was followed to address the beliefs and attitudes of pre-service (undergraduate) and in-service (graduate) teachers toward sexual minorities through an online survey and face-to-face interviews. Group means of the PREJUDICE scale for each independent variable were analyzed for statistical significance. The total variance of the PREJUDICE scale was accounted for by personal characteristics only (political, 38%; religious, 9%; non-heterosexual friends, 18%; and family members, 5%; participant sexual orientation, 8%; and finishing the survey, 6%). Neither demographic nor educational characteristics accounted for statistically significant differences in group means of the PREJUDICE scale. College-level coursework completed in multicultural education did not significantly account for any of the total variance in PREJUDICE scores. Significantly lower levels of sexual prejudice were associated with having non-heterosexual friends and family members or being non-heterosexual, and there were no significant effects from educational interventions. However, one-on-one interviews provided stories of direct experience with sexual minority youth in K-12 classrooms. A majority of qualitative participants had questioned their conservative backgrounds and the familial/societal messages they had received regarding gender and sexual variance. Their questioning was strengthened by having non-heterosexual friends and family members. In addition, several participants had worked directly with sexual minority youth in their own school buildings and classrooms. Had this study been limited to a survey, the lived experiences of these pre-service and in-service teachers would have been lost. Having friends and family members who are non-heterosexual transcended their socialization and facilitated their development as social justice allies.
Keywords: Marginalized; Heteronormativity; Bullying; Schools; Lesbian Gay; Gender; Gender Studies (0733); GLBT Studies (0492); Teacher Education (0530)